Given that ∀ n ∈ N + , x 1 = 2 and i = 1 ∑ n − 1 x i x i + 1 x n 2 = 2 ( x 2 2 − x 1 2 x n 2 − x 1 2 ) for n ≥ 2 , find the value of x 1 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It can be proved inductively that x n = 2 n :
The first case n = 2 is true because i = 1 ∑ 2 − 1 x i x i + 1 x 2 2 = 2 1 ⋅ 2 2 ( 2 2 ) 2 = 2 = 2 x 2 2 − x 1 2 x 2 2 − x 1 2 .
Then assuming the sum for n is true, the sum for n + 1 is also true because:
i = 1 ∑ ( n + 1 ) − 1 x i x i + 1 x n + 1 2
= 2 1 ⋅ 2 2 ( 2 n + 1 ) 2 + 2 2 ⋅ 2 3 ( 2 n + 1 ) 2 + . . . + 2 n ⋅ 2 n + 1 ( 2 n + 1 ) 2
= 2 2 n + 1 ( 2 n + 1 ) 2 ( 2 2 n − 2 + 2 2 n − 4 + . . . + 1 )
= 2 ( 2 2 − 1 2 2 n − 1 )
= 3 2 ( 2 2 n − 1 )
= 3 2 ⋅ 4 4 ( 2 2 n − 1 )
= 2 ⋅ ( 2 2 ) 2 − ( 2 1 ) 2 ( 2 n + 1 ) 2 − 4
= 2 ⋅ x 2 2 − x 1 2 x n + 1 2 − 4
which completes the inductive proof.
Therefore, x 1 0 = 2 1 0 = 1 0 2 4 .
Problem Loading...
Note Loading...
Set Loading...
From the first few x n , it appears that x n = 2 n . Let us prove the claim by induction that the claim is true for all n ≥ 1 . We note that the claim is true for n = 1 and n = 2 . Assuming the it is true for n . Then
k = 1 ∑ n x k x k + 1 x n + 1 2 x n 2 x n + 1 2 k = 1 ∑ n − 1 x k x k + 1 x n 2 + x n x n + 1 x n 2 x n + 1 2 ⋅ 6 x n 2 − 4 + x n x n + 1 x n + 1 2 x n 2 − 4 x n + 1 2 + 6 x n + 1 x n 2 x n + 1 2 − 3 x n + 1 x n − 2 x n 2 ( 2 x n + 1 + x n ) ( x n + 1 − 2 x n ) ⟹ x n + 1 = 2 ( x 2 2 − x 1 2 x n + 1 2 − x 1 2 ) = 6 x n + 1 2 − 4 = 6 x n + 1 2 − 4 = x n + 1 2 x n 2 − 4 x n 2 = 0 = 0 = 2 x n = 2 n + 1 Since x n + 1 ∈ N
Therefore the claim is true for n + 1 and hence true for all n ≥ 1 and x 1 0 = 2 1 0 = 1 0 2 4 .